A Novel OsMPK6‐OsMADS47‐PPKL1/3 Module Controls Grain Shape and Yield in Rice - Jingjing Fang; Yan Chun; Fan Zhang; Tingting Guo; Mengmeng Ren; Jinfeng Zhao; Shoujiang Yuan; Wensheng Wang; Yunhai Li; Xueyong Li (Advanced Science)
Abstract Grain shape is a key determinant of both grain yield and appearance quality in rice. However, the interactions among different regulatory pathways remain unclear. Here, a novel regulatory axis centered on a MADS‐box transcription factor (TF) OsMADS47 for controlling rice grain shape is reported. OsMADS47 overexpression results in slender grains, whereas knockout leads to short and small grains. OsMADS47 acts downstream of the OsMKKK10‐OsMKK4‐OsMPK6 cascade and can be phosphorylated by OsMPK6. Phosphorylation stabilizes OsMADS47 and enhances its transcriptional repression activities on target genes GS3 and GW8, two well‐known grain shape regulators. Meanwhile, the Kelch‐repeat protein phosphatase PPKL1/3 can dephosphorylate OsMADS47, making it unstable and releasing the transcriptional repression on target genes. Knockdown of OsMPK6 or overexpression of PPKL1/3, GS3, or GW8 partially suppresses the slender‐grain phenotype of the OsMADS47 overexpression plants. The results establish an integrated regulation pathway of grain shape and prove the hub gene OsMADS47 as a potential target for breeding rice with optimized appearance quality.